Predicting Factors of Adaptation among Family Caregivers of Patients with Chronic Illnesses by the Empowerment in Patient Care, the Caregivers’ Perception in Patient’s Health Status and Social Support - Laoopugsin, Suwannee; Maneewong, Supranee; Naktes, Chainarong (Journal of health and health management, 2022)
This research aimed at exploring predicting factors of adaptation among family caregivers of patients with chronic illnesses. The sample comprised 198 family caregivers who residing in Sathorn, the urban community in Bangkok. Data were collected by the questionnaires and were analyzed by descriptive and Linear Regression statistics. The results of the study revealed that the majority of the sample were female (65.2%) whose age ranged from 29-67 with the mean age of 55.1. About 42 % of the sample were the patients’ spouse while majority (86.4%) had chronic diseases including musculoskeletal diseases, hypertension, hyperlipidemia, diabetes and cancer. Predicting factors of family caregivers’ adaptation were caregiving ability and social support. Both of these factors can co-predict the variance of adaptation for 57.5%. The predictive model can be composed as follow; Family caregivers’ adaptation = 0.909 - 0.471 caregiving ability - 0 .306 social support + error. From the results of this study, it is recommended that, in order to promote family caregivers’ adaptation, nurses should provide them with proper caregiving information for patients with chronic illnesses. The family caregivers should be encouraged to ensure their confidence in performing patients’ care. Moreover, supports from necessary resources should be provided throughout the caregiving process. In particular, during the first 3 months while the family caregivers are in the early phase of adaptation